Избранное: Стихотворения: Переводы: Статьи / Константин Бальмонт - Бальмонт Константин Дмитриевич (Правда, 1990)
Экземпляры: ф.18 (1991) / Инвентарный номер: 33246 / Цена: / Сис.шифр: 84(2Рос=Рус)1-5 / Авт.знак: Б 21 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)1-5